Big Data as a Driver for Clinical Decision Support Systems: A Learning Health Systems Perspective - Dagliati, Arianna; Tibollo, Valentina; Sacchi, Lucia; Malovini, Alberto; Limongelli, Ivan; Gabetta, Matteo; Napolitano, Carlo; Mazzanti, Andrea; De Cata, Pasquale; Chiovato, Luca; Priori, Silvia; Bellazzi, Riccardo (Frontiers in Digital Humanities, 2018)
Big data technologies are nowadays providing health care with powerful instruments to gather and analyze large volumes of heterogeneous data collected for different purposes, including clinical care, administration and research. This makes possible to design IT infrastructures that favor the implementation of the so-called "Learning Healthcare System Cycle", where healthcare practice and research are part of a unique and synergic process. In this paper we highlight how "Big Data enabled" integrated data collections may support clinical decision-making together with biomedical research. Two effective implementations are reported, concerning decision support in Diabetes and in Inherited Arrhythmogenic Diseases.